2021
DOI: 10.48550/arxiv.2112.05779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Architecture Search via Continual Reinforcement Learning

Abstract: Quantum computing has promised significant improvement in solving difficult computational tasks over classical computers. Designing quantum circuits for practical use, however, is not a trivial objective and requires expert-level knowledge. To aid this endeavor, this paper proposes a machine learning-based method to construct quantum circuit architectures. Previous works have demonstrated that classical deep reinforcement learning (DRL) algorithms can successfully construct quantum circuit architectures withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…There are different technologies to design the different architectures of the circuit by machine learning [88] or reinforcement learning [89,90].…”
Section: Parameter Layermentioning
confidence: 99%
“…There are different technologies to design the different architectures of the circuit by machine learning [88] or reinforcement learning [89,90].…”
Section: Parameter Layermentioning
confidence: 99%
“…Ref. [35] studied quantum state preparation for changing environment by training a reinforcement learning agent that utilizes past policies learned from previous environments.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [35] proposed a continual reinforcement learning framework to deal with the constantly changing environment. In this framework, the agent leverages past policies learned from previous noise environments to generate a state preparation quantum circuit for a new noise environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of some VQAs, to address the challenges of finding the architecture of ansatz, methods have been introduced that draw on the insight and techniques of machine learning [8][9][10][11][12], such as a process of automating the architecture engineering of quantum circuits is known as quantum architecture search (QAS) [9,13,14]. Recent studies have strongly suggested that double deep Q-networks (DDQN) in reinforcement learning (RL) can successfully solve QAS problems [8,10], performance improvement in QAOA variants [15] as well as the task of quantum compiling [16].…”
Section: Introductionmentioning
confidence: 99%